Development of transport system of the Republic of Kazakhstan - Semak, Y.A.; Raimbekov, B.Kh.; Assanova, M.K.; Kozhabergenova, A.Y. (BUKETOV BUSINESS REVIEW, 2017)
The article discusses the state and development of the transport system of the Republic of Kazakhstan at the present stage. Development of the transport system is one of the most important conditions for the further restructuring of the economy of the country and improving the competitiveness of the domestic goods and services in the world markets. The article considers the dynamics of the volume of transport services in recent years: passenger and freight transportation by pipelines. The article shows the importance of transcontinental routes passing through the vast territory of the Republic of Kazakhstan. The article considers the problems of development of the main modes of transport in Kazakhstan: rail and road. It shows a slight amount of water transport services are characterized by geographical features of the terrain and location. The measures to achieve the objectives of the use of the transport potential of the country are listed here . Particular attention is paid to the key companies in the railway sector - JSC «National Company» ҚazaқstanTemіrZholy»». In the article attention is paid to the State program of development and integration of the transport system infrastructure of Kazakhstan until 2020, provided the measures recommended therein. The transport complex of the Republic of Kazakhstan now provides the overall needs of the national economy and population in transport services. However, Kazakhstan has many ways of developing a transport potential.